2010
DOI: 10.1128/aac.00487-10
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin-Oxacillin Combinations in Treatment of Experimental Endocarditis Caused by Daptomycin-Nonsusceptible Strains of Methicillin-Resistant Staphylococcus aureus with Evolving Oxacillin Susceptibility (the “Seesaw Effect”)

Abstract: In vivo development of daptomycin resistance (DAP r ) among Staphylococcus aureus strains, especially methicillin-resistant S. aureus (MRSA) strains, in conjunction with clinical treatment failures, has emerged as a major problem. This has raised the question of DAP-based combination regimens to enhance efficacy against such strains. We studied five recent DAP-susceptible (DAP s )/DAP r clinical MRSA strain pairs obtained from patients who failed DAP monotherapy regimens, as well as one DAP s /DAP r MRSA strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 56 publications
8
109
2
Order By: Relevance
“…The mechanisms for this are not fully understood, but some ␤-lactams have been observed to increase binding of DAP to bacterial cell membranes (3,4) or to target binding to membrane regions where DAP is most effective (5). This is consistent with reports of a DAP-␤-lactam "seesaw effect," whereby S. aureus frequently gains susceptibility to ␤-lactams upon acquisition of the DAP-nonsusceptible (DNS) phenotype (6). Collectively, these in vitro observations have been translated to antimicrobial therapy combinations to successfully manage difficult-to-treat MRSA infections (1,3,6,7).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The mechanisms for this are not fully understood, but some ␤-lactams have been observed to increase binding of DAP to bacterial cell membranes (3,4) or to target binding to membrane regions where DAP is most effective (5). This is consistent with reports of a DAP-␤-lactam "seesaw effect," whereby S. aureus frequently gains susceptibility to ␤-lactams upon acquisition of the DAP-nonsusceptible (DNS) phenotype (6). Collectively, these in vitro observations have been translated to antimicrobial therapy combinations to successfully manage difficult-to-treat MRSA infections (1,3,6,7).…”
supporting
confidence: 74%
“…This is consistent with reports of a DAP-␤-lactam "seesaw effect," whereby S. aureus frequently gains susceptibility to ␤-lactams upon acquisition of the DAP-nonsusceptible (DNS) phenotype (6). Collectively, these in vitro observations have been translated to antimicrobial therapy combinations to successfully manage difficult-to-treat MRSA infections (1,3,6,7).…”
supporting
confidence: 73%
“…We demonstrated that a single mutation in rpoB resulting in an A 477 D substitution in the ␤ subunit of RNA polymerase (RNAP) significantly decreased susceptibility not only to daptomycin but also to vancomycin, ␤-lactams, and rifampin. These results demonstrate that decreased susceptibility to daptomycin is acquired by a pathway conferring high levels of resistance to ␤-lactams, in contrast to other pathways leading to DAP-NS, which have been shown to cause a concomitant fall in ␤-lactam resistance, a phenomenon designated the daptomycin/␤-lactam "seesaw effect" (43). rpoB mutations are common in DAP-NS strains, but to our knowledge, the A 477 D variation has not previously been selected after daptomycin exposure.…”
Section: Discussionmentioning
confidence: 80%
“…Most available data exist on combination therapy with daptomycin and b-lactam antibiotics [95,96]. Oxacillin, in particular, appears to be very efficacious [97,98]. bLactams improve the binding of daptomycin by increasing the net negative charge of the cell membrane [96].…”
Section: Combination Therapy With Daptomycinmentioning
confidence: 99%